2019 EULAR recommendations for the generic core competences of health professionals in rheumatology. Issue 1 (9th August 2019) - Edelaar, Lisa; Nikiphorou, Elena; Fragoulis, George E; Iagnocco, Annamaria; Haines, Catherine; Bakkers, Margot; Barbosa, Lurdes; Cikes, Nada; Ndosi, Mwidimi; Primdahl, Jette; Prior, Yeliz; Pchelnikova, Polina; et al.
Abstract : Background/objectives: To maintain and optimise the quality of care provided by health professionals in rheumatology (HPRs), adequate educational offerings are needed. This task force (TF) aimed to develop evidence-based recommendations for the generic core competences of HPRs, with specific reference to nurses, physical therapists (PTs) and occupational therapists (OTs) to serve as a basis for their postgraduate education. Methods: The EULAR standardised operating procedures for the development of recommendations were followed. A TF including rheumatologists, nurses, PTs, OTs, patient-representatives, an educationalist, methodologists and researchers from 12 countries met twice. In the first TF meeting, 13 research questions were defined to support a systematic literature review (SLR). In the second meeting, the SLR evidence was discussed and recommendations formulated. Subsequently, level of evidence and strength of recommendation were assigned and level of agreement (LoA) determined (0–10 rating scale). Results: Three overarching principles were identified and 10 recommendations were developed for the generic core competences of HPRs. The SLR included 79 full-text papers, 20 of which addressed the competences, knowledge, skills, attitudes and/or educational needs of HPRs from multiple professions. The average LoA for each recommendation ranged from 9.42 to 9.79. Consensus was reached both on a research and educational agenda. Conclusion: Evidence and expert opinion informed a set of recommendations providing guidance on the generic core competences of HPRs. Implementation of these recommendations in the postgraduate education of HPRs at the international and national level is advised, considering variation in healthcare systems and professional roles.